The choice : embrace the possible - Eger, Edith Eva; Weigand, Esmé Schwall (Scribner, 2017)
At the age of sixteen, Edith Eger was sent to Auschwitz. Hours after her parents were killed, Nazi officer Dr. Josef Mengele, forced Edie to dance for his amusement and her survival. Edie was pulled from a pile of corpses when the American troops liberated the camps in 1945. Edie spent decades struggling with flashbacks and survivor<U+2019>s guilt, determined to stay silent and hide from the past. Thirty-five years after the war ended, she returned to Auschwitz and was finally able to fully heal and forgive the one person she<U+2019>d been unable to forgive<U+2014>herself. Edie weaves her remarkable personal journey with the moving stories of those she has helped heal. She explores how we can be imprisoned in our own minds and shows us how to find the key to freedom. The Choice is a life-changing book that will provide hope and comfort to generations of readers.